(untitled) (Research, Society and Development, 2022)
The use of renewable energy sources in various fields of knowledge is a strong global trend, thanks to the numerous socioeconomic and environmental advantages arising from the adoption of sustainable practices, which allow promoting a balance between the preservation of the environment and the well-being of people. being of the current and future population. The development of new technologies based on solar and wind energy has been considered one of the many key solutions to meet the high energy demand worldwide. However, despite the many benefits related to sustainability, the world scenario shows that we still do not have such a sustainable scenario and it is still climbing positions slowly, due to issues that include financial support from the government, research incentives, lack of knowledge of the population, a sustainable vision of entrepreneurs and among other factors. In this work, a systematic literature review was carried out to assess the main measures, trends adopted, and a greater understanding of renewable energy sources. Some advantages and disadvantages involving solar and wind technologies are discussed in this article, to contribute significantly to the list of main practices and perspectives on the generation and production of energy from them. The results of these studies indicate that, despite the investments made, more investments are expected in research and installations of wind farms and better financing conditions for the adhesion of solar panels and wind turbines, aiming to overcome the current limitations of the renewable energy industry, considering given that this is a market that still needs exploration and investment in new research to expand this large area of ​​study.